Whither economic complexity? A new heterodox economic paradigm or just another variation within the mainstream? - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2016)
[Introduction] Economics is in considerable disarray. Neoclassical orthodoxy still remains the `normal science' standard procedure and provides the foundation for economic education. However, for some time now many economists have claimed that its scientific research programme as a problem-solving tool has been squeezed out and is no longer at the cutting-edge of research (see e.g. Colander/Holt/Rosser 2004, Holt/Rosser/Colander 2011, Arthur 2013). After the recent global financial crisis, the time seemed right for a scientific overhaul of the whole discipline of economics under the heading of `new economic thinking`, an idea promoted as much by economists unhappy with the state of the discipline as by economics students unwilling to learn something apparently irrelevant for the real world and by economic and business practitioners and patrons who sponsored research that, in the past, few were willing to support financially. It seems obvious that heterodox economics – the part of the scientific community which had been critical of the state of the discipline long before the outbreak of the global financial crisis and which long before had demanded a `new economic thinking` - could have been seen as a natural candidate for a scientific research programme or paradigm that could assume the spotlight. However, heterodox economics is a blurred description of a scientific paradigm comprising quite different thought collectives and is based on very shaky analytical grounds (see e.g. Mearman 2012). In this contribution, we will take a closer look at a scientific research programme which has often been cited as the one whose time is about to come: complexity economics (see e.g. Buchanan 2004, Colander 2003, Beinhocker 2006, Davis 2008; Roos 2015). Before we attempt to describe the paradigmatic foundations of complexity economics and arrange them in the context of the orthodox/heterodox divide, we need to explain our understanding of the concept of a paradigm and clarify what makes a paradigm orthodox or heterodox and why it is important to classify a paradigm as either orthodox or heterodox. The paper will conclude with a statement about the paradigmatical position of complexity economics and its significance for the future of the economic discipline.
Keywords: 330